Perancangan pindahmilik harta keluarga ke arah pengukuhan kekayaan generasi di Malaysia. - Sulong, Jasni (Universiti Sains Malaysia, 2008)
The management in the distribution of property nowadays is very much important especially to ensure it to be given to the right party peacefully. "The right party" is including our heirs or dependant. Thus it serves as a warranty for their future security, maintain the sustainability of life and enhance their socia-needs which contribute to the paradigm-shift of ummah.